The disreputable history of Frankie Landau-Banks : a novel - Lockhart, E. (New York : Hyperion, 2008)
Sophomore Frankie starts dating senior Matthew Livingston, but when he refuses to talk about the all-male secret society that he and his friends belong to, Frankie infiltrates the society in order to enliven their mediocre pranks.
Includes bibliographical references (p. 343-344).
A Junior Library Guild selection
Keywords: Boarding schools -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Practical jokes -- Juvenile fiction; Clubs -- Juvenile fiction; Boarding schools -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Practical jokes -- Fiction; Clubs -- Fiction; Schools -- Fiction; Secret societies -- Fiction; Sexism -- Fiction; Practical jokes -- Fiction; Interpersonal relationships -- Fiction; Private schools -- Fiction; High schools -- Fiction; School stories; Young adult fiction